Effects of Grazing Intensity on Microbial Diversity at Different Soil Depths in Desert Steppe Soils - Yuxin Wang; Xin Ju; Qian Wu; Guodong Han (Agronomy)
This study examines the influence of grazing intensity on soil microbial communities in a desert steppe ecosystem. Soil samples were collected from three depths (0–10 cm, 10–20 cm, and 20–30 cm) under varying grazing intensities: control (CK), light (LG), moderate (MG), and heavy grazing (HG). Key soil physicochemical properties and plant characteristics were analyzed alongside microbial diversity and community composition, which were assessed by identifying amplicon sequence variants and by conducting linear discriminant analysis effect size. The results showed that grazing intensity significantly impacted soil moisture, organic carbon, total nitrogen, and phosphorus levels, with a notable decrease in plant cover and microbial diversity under heavy grazing. CK and LG treatments supported higher microbial diversity, especially in surface layers, while heavy grazing was associated with a shift in community composition toward stress-tolerant taxa like Acidobacteriota and Blastocatella. Non-metric multidimensional scaling analysis revealed differences in microbial community structure between soil depths, with the effects of grazing diminishing with depth. These findings highlight the critical role of sustainable grazing practices in maintaining soil health and microbial diversity, with implications for the long-term resilience of desert steppe ecosystems.